A review on voltage control methods using on-load tap changer transformers for networks with renewable energy sources - Sarimuthu C.R.; Ramachandaramurthy V.K.; Agileswari K.R.; Mokhlis H. (Elsevier Ltd, 2023)
Electric load flow; Electric power distribution; Local area networks; Power transformers; Renewable energy resources; Automatic voltage control relays; Bidirectional power flow; Distribution network operators; Distribution systems; On-load tap changer transformers; On-load tap changers; Renewable energy source; Reverse Power flows; Voltage control